Diagnosis of occult scaphoid fractures: an exploratory study to assess whether clusters of clinical features are diagnostic in comparison to reduced sequence magnetic resonance imaging - Burton, Christopher; McRae, Bonnie; Kyle, Greg; Nusem, Iulian (Physiotherapy theory and practice, 2025)
Occult scaphoid fractures are difficult to diagnose radiographically. Evidence regarding prevalence and diagnostic accuracy of clinical tests is growing; however, gaps in knowledge remain and further research is needed. This study aimed to determine the prevalence of occult scaphoid fractures and other hand/wrist fractures, plus any clinical/demographic findings diagnostic of scaphoid fractures. Prognostic prospective cohort study. Patients referred with diagnosis of occult scaphoid fractures, non-diagnostic radiographs, and one or more positive provocative test for scaphoid fractures were included. Clinical data were compared to reduce sequence magnetic resonance imaging. Univariate logistic regression was used to determine significance. Multivariable logistic regression was used to determine the effect size of these variables. Of 197 included participants, 43(22%) had a scaphoid fracture and 59(30%) had an occult fracture other than scaphoid. Average age of patients with confirmed occult scaphoid fractures was 22 years old. Distal pole fractures were the most common scaphoid fracture ( = 28/65.1%, average age 16.9 years). Three clinical tests (pain with ulnar-deviation, anatomical snuffbox swelling and pain-free grip) plus two demographics (age <23 and male) resulted in accuracy of 81.7%, positive predictive value of 73.3%, and negative predictive value of 82.4% in diagnosing scaphoid fractures. This study confirms a high prevalence of occult fractures in our population. Patients demonstrating the relevant demographics and positive clinical tests may be appropriate to treat as scaphoid fractures without advanced imaging. Most patients will present with differing clinical findings and/or demographics, and routine use of magnetic resonance imaging is recommended.